Menghadapi Tantangan Modernitas: PKM Berbasis OBE untuk Mengasah Analisis Mahasantri dalam Isu Pemikiran Kontemporer - Elkarimah, Mia Fitriah; Huda, Ade Nailul (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
This Community Service Activity (PKM) aims to strengthen the intellectual capacity of specialised students of Tafsir at Ma'had Aly Attaqwa KH. Noer Alie through the organisation of a general lecture series. The programme is designed to bridge classical scholarly traditions (turats) with modern intellectual challenges by implementing an Outcome-Based Education (OBE) curriculum. This methodology focuses on measurable outcomes, specifically the students' ability to critically examine and analyse contemporary thought, particularly the hermeneutics of Muhammad Syahrur. The results of the activity demonstrate the effectiveness of the OBE approach, as students showed measurable improvements in their analytical and critical thinking skills. They were not only able to scientifically critique new ideas but also strengthened their awareness of the fundamental role of turats as a solid methodological foundation. The key to engaging with new ideas like Syahrur's is a strong mastery of classical scholarly foundations. The main conclusion emphasises that mastery of classical interpretive methodology is an absolute prerequisite for engaging critically and productively with modern thought. Overall, this activity successfully prepared Ma'had Aly students to become ethical, intelligent, and critical Muslim intellectuals. They were equipped with the ability to bridge the gap between the solid intellectual heritage of Islam and the dynamics of their times, enabling them to provide authentic enlightenment and solutions to the community's needs.